Peran Keluarga, Sekolah Dan Masyarakat dalam Mencetak Generasi Ilahiah di Kota Makassar - Sartika Sartika; Hasrianti Hasrianti; Lediana Rosa; Miftakhurahmi Miftakhurahmi (Islamic University of Indonesia, 2022)
Although the majority of Makassar population are Muslim, the current development causes the implementation of Islamic religious values decreasing. Makassar Muslim’s commitment began to be weakened by the ever-increasing influence of others’ customs and cultures. This study aims to determine the urgency of Islamic religious education and the strategies used to instil the values of Islamic religious education in creating a divine generation. The researchers use qualitative research methods in trying to interpret the phenomena that occur through interview and documentation techniques. The result of the study indicates that despite neglected by many, the small circles of Makassar Muslim community is still persistent in carrying out Islamic teachings in. However, there must be holistic strategy to instil Islamic teachings values within the larger society containing the role of family, school, and society.